Traditional Islam and Global Religious Connectivity: Nahdlatul Ulama in The Netherlands - Amin Mudzakkir (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2020)
This article examines the Nahdlatul Ulama in the Netherlands. Nahdlatul Ulama is the largest Muslim organization in Indonesia which is now starting to open branches overseas, including in the Netherlands. Despite its traditional pattern, NU has a religious vision which has been very responsive to global connectivity from the beginning. Based on interviews and observations, this article demonstrates the ability of the Dutch NU to portray itself as a religious diaspora organization that bridges the identity needs of its members regarding the homeland and the reality of daily life in the Dutch multicultural society. Keywords: Nahdlatul Ulama, traditional Islam, religious connectivity, Indonesia, Dutch multicultural society REFERENCE: Anderson, Bennedict R. O’G. 1992. “Long-distance nationalism: World capitalism and the rise of identity politics”. The Wertheim Lecture 1992. CASA-Centre for Asian Studies Amsterdam. Azra, Azyumardi. 1994. Jaringan ulama : Timur Tengah dan kepulauan Nusantara abad XVII dan XVIII : melacak akar-akar pembaruan pemikiran Islam di Indonesia. Bandung: Mizan. Helly, Denise. 2006. “Diaspora: History of an idea” dalam Haideh Moghissi (ed.). Muslim diaspora: Gender, culture and identity. London/New York: Routledge. Laffan, Michael Francis. 2003. Islamic nationhood and colonial Indonesia: The umma below the winds. London/New York: Routledge. Noer, Deliar. 1980. Gerakan Moderen Islam di Indonesia, 1900-1942. Jakarta: LP3ES. Sujadi. 2017. Persatuan Pemuda Muslim se-Eropa: identity, encouragement for giving, and network, 1971-2009, Disertasi Universitas Leiden. Wawancara, Ahmad Maksum Hambali, 9 Maret 2019. Wawancara, Nur Hasyim Sobandi, 12 Maret 2019. Wawancara, Nana Supriatna, 14 Maret 2019. Korespondensi, M. Latif Fauzi, 31 Oktober 2019. https://www.nu.or.id/post/read/107683/konferensi-internasional-nu-belanda-perkuat-promosi-islam-moderat http://nubelanda.nl/conference2019/selected-papers/120-conference2019 https://islam.nu.or.id/post/read/76456/seminar-internasional-islam-nusantara-awali-konfercab-nu-belanda